EXPLORING HOW HR EXPERTISE, ACCOUNTING SKILLS, AND INTERNAL CONTROLS SHAPE THE QUALITY OF FINANCIAL REPORTS - Eka Berliana Zazzabila; Diah Ekaningtyas (Center for Indonesian Accounting Studies, 2025)
Research Objective – This study aims to determine the effect of human resource competency, accounting understanding, and internal control systems on the quality of financial reports in cooperatives in the Lamongan District. Method – The population and sample in this study consist of 53 consumer cooperatives in Lamongan District, using purposive sampling technique. This study uses primary data, with data collection conducted through questionnaires. According to Cooperative Data - Ministry of Cooperatives and SMEs (2022), accessed on October 12, 2022 Main Findings – It is concluded that many cooperatives in Lamongan District have not yet prepared their financial reports in a timely manner, resulting in the inability to report RAT results routinely.Theoretical and Policy Implications – The results of this study indicate that human resource competency affects the quality of financial reports. Accounting understanding does not affect the quality of financial reports. Internal control systems do affect the quality of financial reports. Research Novelty – This study discusses accounting understanding and internal control systems in relation to the quality of financial reports in cooperatives in Lamongan District